2006
DOI: 10.1021/ic0604009
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Magnetic Properties of a Non-Heme Diiron Complex Singly Bridged by a Hydroxo Group

Abstract: The synthesis of the first singly bridged non-heme diiron complex with a mu-hydroxo bridging ligand, [{(salten)Fe}2(OH)][B(C6H5)4].(CH3CN)x.(H2O)y (1) [H2salten = 4-azaheptane-1,7-bis(salicylideneiminate)], is reported. The complex has been characterized with X-ray crystallography, FTIR, magnetic susceptibility measurements, and Mössbauer spectroscopy. The data have been compared with the results of DFT calculations on both 1 and a model with an unsupported mu-oxo bridge (2) to verify the formulation of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 38 publications
2
43
2
Order By: Relevance
“…The highest energy bands (255, 231 nm for 1a; 260, 233 nm for 1b; 256 and 234 nm for 2) are attributed to πǞπ* transitions of the ligand, but contributions from less intense oxido-to-Fe CT are also expected in this region. [12] …”
Section: Ftir and Uv/vis Spectra Of Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest energy bands (255, 231 nm for 1a; 260, 233 nm for 1b; 256 and 234 nm for 2) are attributed to πǞπ* transitions of the ligand, but contributions from less intense oxido-to-Fe CT are also expected in this region. [12] …”
Section: Ftir and Uv/vis Spectra Of Complexesmentioning
confidence: 99%
“…Conversely, the hydroxido bridge is relatively unusual. [12] A fundamental structural component of the chemistry of these functional Fe III complexes is the variable Fe-O-Fe bridging angle, which is usually in the range 139-180°. However, in the majority of complexes where other bridging ligands are [ .…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on iron systems, it has been shown that for supported [38] and unsupported [39] oxo bridged compounds the FeÀO distance is the main parameter which governs the strength of the magnetic interaction. In complex 1, the Fe-(m-OA C H T U N G T R E N N U N G (POM)) distances are long (1.915(11) and 2.106(11) ) compared to those classically found in dinuclear m-O bridged Fe III complexes, which justifies the low J value determined for this compound.…”
mentioning
confidence: 99%
“…[16] In contrast, freshly prepared Cr-1 c exhibits av ery weakb and at ñ = 3590cm À1 that can be assigned to the OH stretcho ft he coordinated water molecule. An older batch of Cr-1 c is characterized by al ower chloride content according to EDXa nalysisa nd exhibits incompletes olubility in THF ( Figure S6), which suggests that the slow loss of HCl with the formation of m-hydroxo-bridged specieso ccurs during storage.…”
Section: Catalysis-related Transformations Of Cr-salphensmentioning
confidence: 98%
“…This behavior is far from ideal living polymerization and suggests www.chemcatchem.org the existence of different catalytic sites that feature asignificant variation in activity,s ometimes even reflectedi nabimodality of PHB samples (see gel-permeationc hromatogram (GPC) in Figure S14). Furthermore, the gross polymerization rate decreaseso nly marginally upon monomer consumption, and this holds true up to high conversions (experiments [13][14][15][16]. This might be because the rate-determining step is independent of the monomer concentration in first approximation,a lthough other explanations can also be given.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%